Complaint & Compliment System (CCS UTP) - Zulhairi, Zulaikha (IRC, 2020)
Nowadays, students tend to post their emotions on social media such as Twitter, Instagram and Facebook. They do not see the after effect of their post towards other people or organization. Thus, this create the idea of having a complaint and compliment system like social media based for Universiti Teknologi PETRONAS (UTP) students. The system will fully utilize the Microsoft tools that the UTP students can access using their UTP email account. The system is a free for the use of students to make complaint in it rather than making complaint in other media social based that will make worldwide users know the negativity of the university system and students. This system also can make students post the compliment for the staffs to show their gratitude towards the hard work of UTP staffs or lecturers. The tools used are PowerApps and Power BI which can integrate a beautiful and user-friendly system for the UTP community to use as their platform to communicate within UTP community. Furthermore, the database for this system will be keep in Microsoft SharePoint which is also one of Microsoft product that is free for UTP community.